The Attitude of Engineering Freshmen Towards Chemistry Teaching in Turkey - SARIER, NİHAL (İstanbul Kültür Üniversitesi Yayınları, 2007)
Although chemistry keeps an important place in the science curricula of primary and secondary educations, studenttypically leave high school with misunderstandings about the nature of matter ,chemical processes, and chemical world. This study aims to identify the attitudes of engineering freshmen towards chemistry in Turkey. It also tries to identify classifications and examples of matter, commonly used by chemistry teachers in secondary schools; those are likely to be misunderstood by students. It offers teachers some suggestions contributing to raise their students awareness of learning chemistry.

İlköğretim ve ortaöğretim fen müfredatlarında kimya önemli bir yer tutmakla birlikte, öğrenciler maddenin doğası, kimyasal süreçler ve kimya dünyası hakkında genellikle yanlış kavrayışlarla liseden mezun olmaktadır. Bu çalışma, Türkiye’de mühendislik birinci sınıf öğrencilerinin kimya ile ilgili yaklaşımlarının belirlenmesini amaçlamaktadır. Ortaöğretimde kimya öğretmenlerinin sıklıkla kullandığı, öğrencilerin yanlış anlaması olası olan madde ile ilgili sınıflandırma ve örnekler belirlenmeye çalışılmıştır. Çalışma, kimya öğreniminde öğrencilerin farkındalık düzeyinin yükseltilmesinde öğretmenlere yardımcı olacak bazı önerileri de ele almaktadır.
Keywords: High School Chemistry; Lise Kimyası; First-year Undergraduate; Lisansta İlk Yıl; Chemical Education Research; Kimyasal Eğitim Araştırma; Misconceptions; Yanlış Anlamalar; Student-Centered Learning; Öğrenci Merkezli Öğrenme